1992
DOI: 10.1007/bf01570719
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glycerol on the growth, adhesion, and cellulolytic activity of rumen cellulolytic bacteria and anaerobic fungi

Abstract: The effect of glycerol on the growth, adhesion, and cellulolytic activity of two rumen cellulolytic bacterial species, Ruminococcus flavefaciens and Fibrobacter succinogenes subsp. succinogenes, and of an anaerobic fungal species, Neocallimastix frontalis, was studied. At low concentrations (0.1-1%), glycerol had no effect on the growth, adhesion, and cellulolytic activity of the two bacterial species. However, at a concentration of 5%, it greatly inhibited their growth and cellulolytic activity. Glycerol did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
1
13

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 15 publications
7
83
1
13
Order By: Relevance
“…Glycerin did not affect the disappearance of the nutritional components of the total ration, especially that of fibre. This finding is in contrast to the results of a study by Roger et al (1992), in which the inclusion of 5% glycerol drastically reduced growth and cellulolytic activity of two bacterial species. In the present study, glycerol at 16% of total DM had positive effects on the disappearance of total ration fibre, contrary to a report that 7.2 or 10.8% of glycerol reduced fibre digestibility (ABO EL-NOR et al, 2010).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Glycerin did not affect the disappearance of the nutritional components of the total ration, especially that of fibre. This finding is in contrast to the results of a study by Roger et al (1992), in which the inclusion of 5% glycerol drastically reduced growth and cellulolytic activity of two bacterial species. In the present study, glycerol at 16% of total DM had positive effects on the disappearance of total ration fibre, contrary to a report that 7.2 or 10.8% of glycerol reduced fibre digestibility (ABO EL-NOR et al, 2010).…”
Section: Resultscontrasting
confidence: 99%
“…The inclusion of glycerol at a concentration higher than 5% of dietary dry matter (DM) may inhibit the in vitro growth of cellulolytic bacteria (ROGER et al, 1992), but studies reported that the inclusion of glycerol at 15% of dietary DM did not affect in vivo neutral detergent fibre digestibility (DONKIN, 2008;AVILA-STAGNO, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…O fato de as bactérias aderidas ao sólido não terem sofrido influência indica que a glicerina não afetou a adesão das bacterias às particulas fibrosas, porém a velocidade de passagem da digesta ruminal provavelmente foi aumentada, implicando redução da população na fase líquida. Essa hipótese dá suporte aos resultados obtidos em pesquisas preliminares em que houve redução na digestibilidade da fibra com o aumento da concentração de glicerina na dieta (Roger et al, 1992;Paggi et al, 2004;Abo El-Nor et al, 2010). Isso porque, se o tempo de permanência das particulas alimentares no rúmen diminuiu, consequentemente o tempo de ação dos microrganismos responsáveis pela degradação da fibra, que possuem crescimento mais lento, reduziu, resultando em diminuição na digestibilidade dessa fração.…”
Section: Resultsunclassified
“…O mecanismo de ação da GB (glicerol) sobre os microrganismos ruminais ainda é desconhecido, porém acreditase que torne o substrato menos acessível às células microbianas (Roger et al, 1992) respectivamente, 632,3; 563,7; 276,8; 56,9; 233,7; 24,80 e 383,7g/dia (Tab. 5).…”
Section: Arqunclassified